CRC handbook of terpenoids: triterpenoids: Volume ii: pentacyclic and hexacyclic triterpenoids - Dev, S.; Gupta, A.S. (CRC Press, 2018)
A compilation of all the known information on terpenoids specifically triterpenoids, is presented in these volumes. The most important available information on a particular compound is discussed, such as its isolation/occurence, available spectral data, and leading references on structural determination. Additionally, triterpenoids synthesis, biosynthesis, proven pharmacological properties, and any known applications are explained. A comprehensive general introduction has been included which surveys the development of triterpenoid chemistry from the beginning to the present. Extremely helpful is the selected list of references to books and reviews dealing with various aspects of triterpenoid chemistry